Interview: Uncrossing paths in a Living Pharmacy implementation at Promissão/SP: Andresa Baja - De Angelis, Luiza Paiva [UNESP]; Carlessi, Pedro Crepaldi (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2023)
In this interview, Andresa Baja presents the path taken by the city of Promissão/SP in the implementation of the Live Pharmacy program.
Caminhos que se bifurcam na implementação de uma Farmácia Viva em Promissão/SP: Uma entrevista com a farmacêutica Andresa Baja
Keywords: Health System; Herbal medicine; Medicinal plants